Developing the Resilience Framework for Nursing and Healthcare - Janice M. Morse; Jacqueline Kent-Marvick; Lisa A. Barry; Jennifer Harvey; Esther Narkie Okang; Elizabeth A. Rudd; Ching-Yu Wang; Marcia R. Williams (SAGE Publishing, 2021)
Despite four decades of resilience research, resilience remains a poor fit for practice as a scientific construct. Using the literature, we explored the concepts attributed to the development of resilience, identifying those that mitigate symptoms of distress caused by adversity and facilitate coping in seven classes of illness: transplants, cancer, mental illness, episodic illness, chronic and painful illness, unexpected events, and illness within a dyadic relationship. We identified protective, compensatory, and challenge-related coping-concept strategies that healthcare workers and patients use during the adversity experience. Healthcare-worker assessment and selection of appropriate coping concepts enable the individual to control their distress, resulting in attainment of equanimity and the state of resilience, permitting the resilient individual to work toward recovery, recalibration, and readjustment. We inductively developed and linked these conceptual components into a dynamic framework, The Resilience Framework for Nursing and Healthcare , making it widely applicable for healthcare across a variety of patients.